2022
DOI: 10.3389/fmicb.2022.981288
|View full text |Cite
|
Sign up to set email alerts
|

Proper irrigation amount for eggplant cultivation in a solar greenhouse improved plant growth, fruit quality and yield by influencing the soil microbial community and rhizosphere environment

Abstract: Water scarcity is a worldwide problem, and in order to obtain plenty of production, agricultural irrigation water accounts for a large portion. Many studies have shown that the interaction of root microorganisms and soil can promote crop growth. Developing ways to reduce irrigation to maintain soil fertility and ensure crop yield by regulating the root microenvironment is an important research goal. Here, we developed a reasonable irrigation plan for eggplant cultivation in a solar greenhouse. The maximum theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Moreover, our study also found that the relative abundance of Streptomyces was positively correlated with the total soluble solids, starch, vitamin C, and total protein contents of pumpkin. Our result is consistent with a previous report by Ji et al [58].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our study also found that the relative abundance of Streptomyces was positively correlated with the total soluble solids, starch, vitamin C, and total protein contents of pumpkin. Our result is consistent with a previous report by Ji et al [58].…”
Section: Discussionsupporting
confidence: 94%
“…Different irrigation volumes were applied in different phenological stages according to the Biologische Bundesanstalt, Bundessortenamt und Chemische Industrie (BBCH) scale index. The definition of the optimal requirement of water per plant was estimated according to previous works [33,34]. Particularly, the irrigation volume employed for the control IR100 was calculated following the model of "FAO irrigation and drainage paper number 56" proposed by Allen et al [35].…”
Section: Differential Irrigation Set-upmentioning
confidence: 99%
“…Seema et al (2022);Ji et al (2022) Betageri and Kottiswaran (2019). reported higher yields of 83.3 t ha -1 under 80% ET 0 level and 100% RDF in addition saving 16.17% of water with mulch compared to without mulch condition in sandy clay loam soils of Coimbatore.…”
mentioning
confidence: 93%